SOSIALISASI URGENSI PENDAFTARAN HAK MEREK GUNA MEMBANGUN KEKUATAN DAN PERLINDUNGAN USAHA MIKRO KECIL DAN MENENGAH DALAM DAYA SAING DI ERA GLOBALISASI - Damarani, Nurul Iqrain; Kirani, Khansa Najmah; Cloudya, Barbara; Setiadi, Salwa Fathin; Fa'adillah, Daffa; Pollatu, Stacey Kharin Cheline; Rensa, Laura Adinda; Zakaria, Salsabila Anggraini; Saharany, Ailsa Novelita; Pebrianti, Kalista Revana; Rahmadhani, Aulia; Tsabitha, Andara; Gafar, Adinda Aulia Rohma; Maksumiyyah, Alfi Zayyan Al; Purba, Yosua Kervin; Zakia, Safira Putri; Aryana, Rizka Afi (Jurnal Kreatif : Karya Pengabdian untuk Masyarakat Aktif dan Inovatif, 2025)
In the increasingly competitive era of globalization in the trading industry, brand protection has become a very important aspect for Micro, Small and Medium Enterprises (MSMEs). Trademark registration is a strategy that is really needed because it is an effort to build strength and protection for MSME owners. Brand registration can not only provide a clear identity for the product, but also protect intellectual property rights, which is very necessary in maintaining competitiveness in the global market. The writing of this article examines the registration of certified marks as an effort to build legal strength and protection for MSME owners, because currently there are many legal violations found in the form of copying brands to gain instant profits or discredit other brands. Therefore, through this study, it is hoped that effective strategies can be found for MSMEs to be able to utilize brand registration to increase business value to face global challenges and can raise awareness for MSMEs to protect their brands so that they are able to adapt and compete at the international level.